Effects of substrate temperature on the degradation of RF sputtered NiO properties. (1st June 2017) - Ahmed, Anas A.; Devarajan, Mutharasu; Afzal, Naveed
Abstract: Nickel oxide (NiO) film was grown on Si (100) substrate through RF sputtering of NiO target in Ar plasma at various temperatures ranging from room temperature (RT) to 300 °C. The structural study revealed (200) oriented NiO diffraction peak at RT and at 100 °C, however, by increasing the substrate temperature to 200 °C, intensity of (200) NiO diffraction peak was decreased. At higher temperature (300 °C), crystalline quality of NiO was significantly degraded and the film was decomposed into Ni. The EDS results confirmed an increase of Ni atomic percentage with increase of the substrate temperature. The surface morphology of NiO film at RT and at 100 °C displayed cubical like grains that were changed into elongated grains with further increase of the substrate temperature. The UV–vis reflectance measurements of NiO revealed a small decrease in its band gap by increasing the substrate temperature to 200 °C.